Probable amoxicillin-associated DRESS syndrome with respiratory manifestations: a case report and systematic review - Genetu Dagnaw Alemayehu; Shimels Getaneh Weldemedhn; Walelign Worku Mamo; Getachew Bizuneh Aydagnuhm; Nathan Kefelegn Woldearegay; Adane Alemayehu Abera; Mequannet Tesfaw Addis; Behaylu Tesfamaryam Hagos (BMC Pulmonary Medicine, 2026)
Abstract Background Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome is a rare but potentially life-threatening drug reaction characterized by cutaneous eruption, hematologic abnormalities and other multiorgan involvement. This condition generally develops after the use of anticonvulsants, allopurinol, or sulfonamides. Despite amoxicillin being commonly prescribed, it is an uncommon cause of DRESS syndrome, and respiratory involvement remains infrequently reported. We present, to our knowledge, the first reported Ethiopian case of probable amoxicillin-associated DRESS syndrome with respiratory manifestations, together with a systematic review of published cases to define its clinical characteristics, diagnostic challenges, and therapeutic outcomes in a resource-limited clinical setting. Methods We performed a systematic review according to the PRISMA standards through PubMed/MEDLINE, Google Scholar, Embase, and Scopus databases up to March 2026. From the literature search, 63 articles were initially identified. Eligibility criteria include: (1) presence of case reports or case series involving DRESS syndrome, (2) amoxicillin as one of the causative drugs, (3) diagnosis supported by RegiSCAR criteria or its equivalent validated tool, and (4) English-language articles only. The quality assessment of the selected case reports was done using the Critical Appraisal Checklist for Case Reports from the Joanna Briggs Institute (JBI). we describe an index case of DRESS due to amoxicillin according to the CARE guidelines. Results After JBI quality assessment of 13 eligible studies, 11 published case reports were included, plus our index case, yielding a total of 12 cases for descriptive synthesis. Our index case involved a 23-year-old female patient of Ethiopian descent who presented with DRESS syndrome on day 7 of amoxicillin monotherapy for tonsillopharyngitis, presenting with morbilliform rash (≈ 72% BSA), fever (38.5 °C), facial and periorbital edema, tachypnea, tachycardia, hypoxemia (oxygen saturation of 84–86%) and bilateral crackles on chest auscultation. The patient’s laboratory tests revealed eosinophilia (850/µl) and mild transaminitis. Chest x-ray revealed bilateral perihilar and lower lobe zone patchy airspace opacities. The RegiSCAR score was 5 (probable DRESS). Among 12 pooled cases, the latency period was between 3 days and 5 weeks; isolated amoxicillin-induced DRESS was seen in 5 cases (41.7%); pulmonary involvement was found in 3 cases (25.0%); and all have favorable outcomes. Conclusion A high index of suspicion is needed for DRESS syndrome for patients presented with fever, rash, and other systemic symptoms following widely used antibiotics like amoxicillin. This study demonstrates that amoxicillin monotherapy can trigger DRESS and clinically significant respiratory involvement can occur independent of hepatic or renal dysfunction. Early recognition, prompt drug discontinuation, systemic corticosteroid therapy, and enhanced pharmacovigilance are essential to improve patient safety and outcomes.